“Live like a Man:” Analysing The White Tiger’s Balram Halwai in a Patriarchal India (Literary Voice, 2024)
Gender, as a socially constructed role that societies assign to individuals based on their perceived sex, has been significantly influenced by social and cultural norms throughout history (Connell 1987, 70). In patriarchal societies like India, the concept of masculinity is particularly shaped by the prevailing social and cultural factors. This paper presents a comprehensive analysis of masculinity through the character of Balram Halwai in Arvind Adiga’s The White Tiger (2008). The primary focus of this study lies in exploring how rigid gender roles contribute to the perpetuation of child abuse and child labour under the guise of upholding “masculinity.” By employing R.W. Connell's theory of masculinities, Judith Butler's theory of gender performativity, structural functionalism perspectives on gender, the paper delves into the character of Balram Halwai to investigate the profound impact that social expectations and gender roles have on his psyche. Furthermore, the paper investigates the extreme measures Balram undertakes in his pursuit of embodying the societal ideals of being a “man.” This study offers an intricate multidimensional exploration of masculinity in a patriarchal Indian context, uncovering the ways in which social expectations and gender roles can profoundly impact individuals’ lives.
Keywords: Child Labour, Child Abuse, Masculinity, Gender, Freedom, Murder